2021
DOI: 10.1101/2021.02.09.21251436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The global distribution of COVID-19 vaccine: The role of macro-socioeconomics measures

Abstract: Since coronavirus disease 2019 (covid-19) has continued to spread globally, many countries have progressed clinical trials and started vaccinations at the end of December 2020. This report aims to analyze the association of COVID-19 vaccine distribution and two macro-socioeconomics measures, including human development index (HDI) and Gross domestic product (GDP), among 25 countries till the first week of February 2021. Our results indicate that a higher GDP per Capita is positively associated with higher COVI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
2
9
1
Order By: Relevance
“…These findings are in line with those of previous studies [43,44]. More specifically, Duan et al [43] carried out a cross-sectional ecological study and analyzed the association between country income level and COVID-19 vaccination coverage rates in 138 countries in terms of the mediating role of vaccination policies.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with those of previous studies [43,44]. More specifically, Duan et al [43] carried out a cross-sectional ecological study and analyzed the association between country income level and COVID-19 vaccination coverage rates in 138 countries in terms of the mediating role of vaccination policies.…”
Section: Discussionsupporting
confidence: 90%
“…Prior to widespread vaccine allocation by COVAX, a large number of studies expressed concern about the fact that the majority of global vaccine purchases and vaccinations were occurring in a few high-income countries [ 7 , 26 , 27 ]. A study analyzing the relationship between macro-socioeconomic factors and the global allocation of COVID-19 vaccines showed that higher gross domestic product per capita was associated with larger numbers of vaccinations [ 28 ], and similar findings were also observed within the United States [ 29 ]. A few studies focused on the different stages of vaccination policies in different countries, which showed that the poorest countries were often lagging behind in with clear strategies or resources to promote COVID-19 vaccination [ 30 ].…”
Section: Discussionmentioning
confidence: 77%
“…However, many factors may influence the efficiency and speed of vaccine rollout, which lagged some states considerably behind the average. Although it is well known that socioeconomic (SES) determinants have a tremendous impact on a faster vaccine rate globally (2), there are limited studies that examine the relationship between SES and vaccine level at a state level. Previous studies show that COVID-19 has impacted those economically disadvantaged (3); therefore, achieving vaccine equality and equity are crucial factors that can protect more vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%